Nonreciprocal frequency conversion with chiral Λ-type atoms - Lei Du; Yao-Tong Chen; Yong Li (Physical Review Research, 2021)
In this paper, we begin with a model of a Λ-type atom whose both transitions are chirally coupled to a wave guide and then extend the model to its giant-atom version. We investigate the single-photon scatterings of the giant-atom model in both the Markovian and the non-Markovian regimes. It is shown that the chiral atom-wave-guide couplings enable nonreciprocal, reflectionless, and efficient frequency conversion, while the giant-atom structure introduces intriguing interference effects to the scattering behaviors, such as ultranarrow scattering windows. The chiral giant-atom model exhibits quite different scattering spectra in the two regimes and, in particular, demonstrates non-Markovicity-induced nonreciprocity under specific conditions. These phenomena can be understood from the effective detuning and decay rate of the giant-atom model. We believe that our results have potential applications in integrated photonics and quantum network engineering.